Molecular-scale synchrotron X-ray investigations of solid-liquid interfaces in lithium-ion batteries - Cao, Chuntian; Steinrück, Hans-Georg (Reference Module in Chemistry, Molecular Sciences and Chemical Engineering)

Comparing transmission- and epi-BCARS: a round robin on solid-state materials - Hempel, Franz; Vernuccio, Federico; König, Lukas; Buschbeck, Robin; Rüsing, Michael; Cerullo, Giulio; Polli, Dario; Eng, Lukas M. (Applied Optics)
Broadband coherent anti-Stokes Raman scattering (BCARS) is a powerful spectroscopy method combining high signal intensity with spectral sensitivity, enabling rapid imaging of heterogeneous samples in biomedical research and, more recently, in crystalline materials. However, BCARS encounters spectral distortion due to a setup-dependent non-resonant background (NRB). This study assesses BCARS reproducibility through a round robin experiment using two distinct BCARS setups and crystalline materials with varying structural complexity, including diamond, 6H-SiC, KDP, and KTP. The analysis compares setup-specific NRB correction procedures, detected and NRB-removed spectra, and mode assignment. We determine the influence of BCARS setup parameters like pump wavelength, pulse width, and detection geometry and provide a practical guide for optimizing BCARS setups for solid-state applications.
Keywords: Atomic and Molecular Physics; and Optics; Engineering (miscellaneous); Electrical and Electronic Engineering

Association of dietary patterns with diabetes-related comorbidities varies among diabetes endotypes - Weber, Katharina S.; Schlesinger, Sabrina; Lang, Alexander; Straßburger, Klaus; Maalmi, Haifa; Zhu, Anna; Zaharia, Oana-Patricia; Strom, Alexander; Bönhof, Gidon J.; Goletzke, Janina; Trenkamp, Sandra; Wagner, Robert; et al. (Nutrition, Metabolism and Cardiovascular Diseases)
Keywords: Cardiology and Cardiovascular Medicine; Nutrition and Dietetics; Endocrinology; Diabetes and Metabolism; Medicine (miscellaneous)

COVID-19 in Female and Male Athletes: Symptoms, Clinical Findings, Outcome, and Prolonged Exercise Intolerance—A Prospective, Observational, Multicenter Cohort Study (CoSmo-S) - Widmann, Manuel; Gaidai, Roman; Schubert, Isabel; Grummt, Maximilian; Bensen, Lieselotte; Kerling, Arno; Quermann, Anne; Zacher, Jonas; Vollrath, Shirin; Bizjak, Daniel Alexander; Beckendorf, Claudia; Egger, Florian; et al. (Sports Medicine)
Abstract Background An infection with SARS-CoV-2 can lead to a variety of symptoms and complications, which can impair athletic activity. Objective We aimed to assess the clinical symptom patterns, diagnostic findings, and the extent of impairment in sport practice in a large cohort of athletes infected with SARS-CoV-2, both initially after infection and at follow-up. Additionally, we investigated whether baseline factors that may contribute to reduced exercise tolerance at follow-up can be identified. Methods In this prospective, observational, multicenter study, we recruited German COVID elite-athletes (cEAs, n = 444) and COVID non-elite athletes (cNEAs, n = 481) who tested positive for SARS-CoV-2 by PCR (polymerase chain reaction test). Athletes from the federal squad with no evidence of SARS-CoV-2 infection served as healthy controls (EAcon, n = 501). Questionnaires were used to assess load and duration of infectious symptoms, other complaints, exercise tolerance, and duration of training interruption at baseline and at follow-up 6 months after baseline. Diagnostic tests conducted at baseline included resting and exercise electrocardiogram (ECG), echocardiography, spirometry, and blood analyses. Results Most acute and infection-related symptoms and other complaints were more prevalent in cNEA than in cEAs. Compared to cEAs, EAcon had a low symptom load. In cNEAs, female athletes had a higher prevalence of complaints such as palpitations, dizziness, chest pain, myalgia, sleeping disturbances, mood swings, and concentration problems compared to male athletes ( p < 0.05). Until follow-up, leading symptoms were drop in performance, concentration problems, and dyspnea on exertion. Female athletes had significantly higher prevalence for symptoms until follow-up compared to male. Pathological findings in ECG, echocardiography, and spirometry, attributed to SARS-CoV-2 infection, were rare in infected athletes. Most athletes reported a training interruption between 2 and 4 weeks (cNEAs: 52.9%, cEAs: 52.4%), while more cNEAs (27.1%) compared to cEAs (5.1%) had a training interruption lasting more than 4 weeks ( p < 0.001). At follow-up, 13.8% of cNEAs and 9.9% of cEAs ( p = 0.24) reported their current exercise tolerance to be under 70% compared to pre-infection state. A persistent loss of exercise tolerance at follow-up was associated with persistent complaints at baseline, female sex, a longer break in training, and age > 38 years. Periodical dichotomization of the data set showed a higher prevalence of infectious symptoms such as cough, sore throat, and coryza in the second phase of the pandemic, while a number of neuropsychiatric symptoms as well as dyspnea on exertion were less frequent in this period. Conclusions Compared to recreational athletes, elite athletes seem to be at lower risk of being or remaining symptomatic after SARS-CoV-2 infection. It remains to be determined whether persistent complaints after SARS-CoV-2 infection without evidence of accompanying organ damage may have a negative impact on further health and career in athletes. Identifying risk factors for an extended recovery period such as female sex and ongoing neuropsychological symptoms could help to identify athletes, who may require a more cautious approach to rebuilding their training regimen. Trial Registration Number DRKS00023717; 06.15.2021—retrospectively registered.
Keywords: Physical Therapy; Sports Therapy and Rehabilitation; Orthopedics and Sports Medicine

Swing-up dynamics in quantum emitter cavity systems: Near ideal single photons and entangled photon pairs - Heinisch, Nils; Köcher, Nikolas; Bauch, David; Schumacher, Stefan (Physical Review Research)

Low-noise balanced homodyne detection with superconducting nanowire single-photon detectors - Protte, Maximilian; Schapeler, Timon; Sperling, Jan; Bartley, Tim (Optica Quantum)
Superconducting nanowire single-photon detectors (SNSPDs) have been widely used to study the discrete nature of quantum states of light in the form of photon-counting experiments. We show that SNSPDs can also be used to study continuous variables of optical quantum states by performing homodyne detection at a bandwidth of 400 kHz. By measuring the interference of a continuous-wave field of a local oscillator with the field of the vacuum state using two SNSPDs, we show that the variance of the difference in count rates is linearly proportional to the photon flux of the local oscillator over almost five orders of magnitude. The resulting shot-noise clearance of (46.0 ± 1.1) dB is the highest reported clearance for a balanced optical homodyne detector, demonstrating their potential for measuring highly squeezed states in the continuous-wave regime. In addition, we measured a CMRR = 22.4 dB. From the joint click counting statistics, we also measure the phase-dependent quadrature of a weak coherent state to demonstrate our device’s functionality as a homodyne detector.

Manipulating spectral topology and exceptional points by nonlinearity in non-Hermitian polariton systems - Wingenbach, Jan; Schumacher, Stefan; Ma, Xuekai (Physical Review Research, in press)

Effect of DNA Origami Nanostructures on Bacterial Growth - Garcia-Diosa, Jaime Andres; Grundmeier, Guido; Keller, Adrian (ChemBioChem)
DNA origami nanostructures are a powerful tool in biomedicine and can be used to combat drug‐resistant bacterial infections. However, the effect of unmodified DNA origami nanostructures on bacteria is yet to be elucidated. With the aim to obtain a better understanding of this phenomenon, the effect of three DNA origami shapes, i.e., DNA origami triangles, six‐helix bundles (6HBs), and 24‐helix bundles (24HBs), on the growth of Gram‐negative Escherichia coli and Gram‐positive Bacillus subtilis is investigated. These results reveal that while triangles and 24HBs can be used as a source of nutrients by E. coli and thereby promote population growth, their effect is much smaller than that of genomic single‐ and double‐stranded DNA. However, no effect on E. coli population growth is observed for the 6HBs. On the other hand, B. subtilis does not show any significant changes in population growth when cultured with the different DNA origami shapes or genomic DNA. The detailed effect of DNA origami nanostructures on bacterial growth thus depends on the competence signals and uptake mechanism of each bacterial species, as well as the DNA origami shape. This should be considered in the development of antimicrobial DNA origami nanostructures.
Keywords: Organic Chemistry; Molecular Biology; Molecular Medicine; Biochemistry

Photochemical Reaction Enabling the Engineering of Photonic Spin−Orbit Coupling in Organic-Crystal Optical Microcavities - Liang, Qian; Ma, Xuekai; Gu, Chunling; Ren, Jiahuan; An, Cunbin; Fu, Hongbing; Schumacher, Stefan; Liao, Qing (Journal of the American Chemical Society (JACS))

Topological edge and corner states in coupled wave lattices in nonlinear polariton condensates - Schneider, Tobias; Gao, Wenlong; Zentgraf, Thomas; Schumacher, Stefan; Ma, Xuekai (Nanophotonics)

Equivalent-circuit model that quantitatively describes domain-wall conductivity in ferroelectric lithium - Zahn, Manuel; Beyreuther, Elke; Kiseleva, Iuliia; Lotfy, Ahmed Samir; McCluskey, Conor J.; Maguire, Jesi R.; Suna, Ahmet; Rüsing, Michael; Gregg, J. Marty; Eng, Lukas M. (Physical Review Applied)
Ferroelectric domain wall (DW) conductivity (DWC) can be attributed to two separate mechanisms: (a) the injection/ejection of charge carriers across the Schottky barrier formed at the (metal-)electrode-DW junction and (b) the transport of those charge carriers along the DW. Current-voltage (I-U) characteristics, recorded at variable temperatures from LiNbO3 (LNO) DWs, are clearly able to differentiate between these two contributions. Practically, they allow us to directly quantify the physical parameters relevant to the two mechanisms (a) and (b) mentioned above. These are, for example, the resistance of the DW, the saturation current, the ideality factor, and the Schottky barrier height of the electrode-DW junction. Furthermore, the activation energies needed to initiate the thermally activated electronic transport along the DWs can be extracted. In addition, we show that electronic transport along LNO DWs can be elegantly viewed and interpreted in an adapted semiconductor picture based on a double-diode, double-resistor equivalent-circuit model, the R2D2 model. Finally, our R2D2 model was checked for its universality by successfully fitting the I-U curves of not only z-cut LNO bulk DWs, but equally of z-cut thin-film LNO DWs, and of x-cut thin-film DWs as reported in literature.
Keywords: General Physics and Astronomy

Charge transfer in superbase n-type doping of PCBM induced by deprotonation - Dong, Chuan-Ding; Bauch, Fabian; Hu, Yuanyuan; Schumacher, Stefan (Physical Chemistry Chemical Physics)
Charge transfer mechanism in the deprotonation-induced n-type doping of PCBM.
Keywords: Physical and Theoretical Chemistry; General Physics and Astronomy

Mehrsprachigkeit in der Schule. Sprachbildung im und durch Sachunterricht.

Tailored second harmonic generation inTi-diffused PPLN waveguides usingmicro-heaters - Babai-Hemati, Jonas; vom Bruch, Felix; Herrmann, Harald; Silberhorn, Christine (Optics Express)
Keywords: Atomic and Molecular Physics; and Optics

Roadmap on electromagnetic metamaterials and metasurfaces - Cui, Tie Jun; Zhang, Shuang; Alu, Andrea; Wegener, Martin; Pendry, John; Luo, Jie; Lai, Yun; Wang, Zuojia; Lin, Xiao; Chen, Hongsheng; Chen, Ping; Wu, Rui-Xin; et al. (Journal of Physics: Photonics)
Keywords: Electrical and Electronic Engineering; Atomic and Molecular Physics; and Optics; Electronic; Optical and Magnetic Materials

ADMM-TGV image restoration for scientific applications with unbiased parameter choice - Zietlow, Christian; Lindner, Jörg (Numerical Algorithms)

Soziologie des Flitzers - Riedl, Lars (Kölner Zeitschrift für Soziologie und Sozialpsychologie)

Insights into the First Multi-Transition-Metal Containing Ruddlesden Popper-Type Cathode for all-solid-state Fluoride Ion Batteries - Vanita, Vanita; Waidha, Aamir Iqbal; Vasala, Sami; Puphal, Pascal; Schoch, Roland; Glatzel, Pieter; Bauer, Matthias; Clemens, Oliver (Journal of Materials Chemistry A)
Promising cathode materials for fluoride-ion batteries (FIBs) are 3d transition metal containing oxides with Ruddlesden-Popper-type structure. So far, multi-elemental compositions were not investigated, but could alternate electrochemical performance similar to what has been found for cathode materials for lithium-ion batteries. Within this study, we investigate RP type La2Ni0.75Co0.25O4.08 as an intercalation-based active cathode material for all-solid-state FIBs. We determine the structural changes of La2Ni0.75Co0.25O4.08 during fluoride intercalation / de-intercalation by ex-situ X-ray diffraction, which showed that F- insertion leads to transformation of the parent phase to three different phases. Changes in Ni and Co oxidation states and coordination environment were examined by X-ray absorption spectroscopy and magnetic measurements in order to understand the complex reaction behaviour of the phases in detail, showing that the two transition metals behave differently in the charging and discharging process. Under optimized operating conditions, a cycle life of 120 cycles at a critical cut-off capacity of 40 mAh g-1 against Pb/PbF2 was obtained, which is one of the highest observed for intercalation electrode materials in FIBs so far. The average Coulombic efficiencies ranged from 85% to 90%. Thus, La2Ni0.75Co0.25O4.08 could be a promising candidate for cycling-stable high-energy cathode materials for all-solid-state FIBs
Keywords: General Materials Science; Renewable Energy; Sustainability and the Environment; General Chemistry

A Comparative Kinetic and Computational Investigation of the Carbon‐Sulfur Cross Coupling of Potassium Thioacetate and 2‐Bromo Thiophene Using Palladium/Bisphosphine Complexes - Peschtrich, Sebastian; Schoch, Roland; Kuckling, Dirk; Paradies, Jan (European Journal of Organic Chemistry)
Abstract We conducted an investigation into the palladium‐catalyzed carbon‐sulfur cross‐coupling reaction involving a 2‐bromothiophene derivative and potassium thioacetate as a substitute for hydrogen sulfide. This investigation utilized kinetic and computational methods. We synthesized two palladium complexes supported by the bisphosphane ligands bis(diphenylphosphino)ferrocene (DPPF) and bis(diisopropylphosphino)ferrocene (D i PPF), as well as their tentative intermediates in the catalytic cycle. Reaction rates were measured and then compared to computational predictions.
Keywords: Organic Chemistry; Physical and Theoretical Chemistry

Synthesis of Ferrocenyl Boranes and their Application as Lewis Acids in Epoxide Rearrangements - Köring, Laura; Birenheide, Bernhard; Krämer, Felix; Wenzel, Jonas O.; Schoch, Roland; Brehm, Martin; Breher, Frank; Paradies, Jan (European Journal of Inorganic Chemistry)
A series of substituted ferrocenyl boron derivatives was synthesized. The oxidation of the ferrocenyl unit resulted in a significant increase of the boron‐centered Lewis acidity. The neutral and cationic Lewis acids were characterized by NMR‐spectroscopy, crystal structure analysis and by computational methods. The new Lewis acids were then applied in the Meinwald rearrangement of epoxides, predominantly furnishing aldehydes as the kinetic products.
Keywords: Inorganic Chemistry

Dynamics of Electron–Hole Coulomb Attractive Energy and Dipole Moment of Hot Excitons in Donor–Acceptor Polymers - Bauch, Fabian; Dong, Chuan-Ding; Schumacher, Stefan (The Journal of Physical Chemistry C)
Keywords: Surfaces; Coatings and Films; Physical and Theoretical Chemistry; General Energy; Electronic; Optical and Magnetic Materials

Ernährung und Alltagsbewältigung - Ein Spannungsfeld für Individuum, Haushalt und Gesellschaft - Buyken, Anette; Libuda, Lars (DGEwissen)

Electrochemical Removal of HF from Carbonate-based LiPF6-containing Li-ion Battery Electrolytes - Ge, Xiaokun; Huck, Marten; Kuhlmann, Andreas; Tiemann, Michael; Weinberger, Christian; Xu, Xiaodan; Zhao, Zhenyu; Steinrueck, Hans-Georg (Journal of The Electrochemical Society)
Due to the hydrolytic instability of LiPF6 in carbonate-based solvents, HF is a typical impurity in Li-ion battery electrolytes. HF significantly influences the performance of Li-ion batteries, for example by impacting the formation of the solid electrolyte interphase at the anode and by affecting transition metal dissolution at the cathode. Additionally, HF complicates studying fundamental interfacial electrochemistry of Li-ion battery electrolytes, such as direct anion reduction, because it is electrocatalytically relatively unstable, resulting in LiF passivation layers. Methods to selectively remove ppm levels of HF from LiPF6-containing carbonate-based electrolytes are limited. We introduce and benchmark a simple yet efficient electrochemical in situ method to selectively remove ppm amounts of HF from LiPF6-containing carbonate-based electrolytes. The basic idea is the application of a suitable potential to a high surface-area metallic electrode upon which only HF reacts (electrocatalytically) while all other electrolyte components are unaffected under the respective conditions.
Keywords: Materials Chemistry; Electrochemistry; Surfaces; Coatings and Films; Condensed Matter Physics; Renewable Energy; Sustainability and the Environment; Electronic; Optical and Magnetic Materials

Decomposing large unitaries into multimode devices of arbitrary size - Arends, Christian; Wolf, Lasse Lennart; Meinecke, Jasmin; Barkhofen, Sonja; Weich, Tobias; Bartley, Tim (Physical Review Research)
Keywords: General Physics and Astronomy

Pillar[5]arene-based dually crosslinked supramolecular gel as a sensor for the detection of adiponitrile - Rodin, Maksim; Helle, David; Kuckling, Dirk (Polymer Chemistry)
An SPR-based dually crosslinked gel sensor for adiponitrile bearing pillar[5]arene responsive sites with a low limit of detection was developed.
Keywords: Organic Chemistry; Polymers and Plastics; Biochemistry; Bioengineering

Derivation of Miller's rule for the nonlinear optical susceptibility of a quantum anharmonic oscillator - Meyer, Maximilian Tim; Schindlmayr, Arno (Journal of Physics B: Atomic, Molecular and Optical Physics)
Miller's rule is an empirical relation between the nonlinear and linear optical coefficients that applies to a large class of materials but has only been rigorously derived for the classical Lorentz model with a weak anharmonic perturbation. In this work, we extend the proof and present a detailed derivation of Miller's rule for an equivalent quantum-mechanical anharmonic oscillator. For this purpose, the classical concept of velocity-dependent damping inherent to the Lorentz model is replaced by an adiabatic switch-on of the external electric field, which allows a unified treatment of the classical and quantum-mechanical systems using identical potentials and fields. Although the dynamics of the resulting charge oscillations, and hence the induced polarizations, deviate due to the finite zero-point motion in the quantum-mechanical framework, we find that Miller's rule is nevertheless identical in both cases up to terms of first order in the anharmonicity. With a view to practical applications, especially in the context of ab initio calculations for the optical response where adiabatically switched-on fields are widely assumed, we demonstrate that a correct treatment of finite broadening parameters is essential to avoid spurious errors that may falsely suggest a violation of Miller's rule, and we illustrate this point by means of a numerical example.

Characterizing Microheterogeneity in Liquid Mixtures via Local Density Fluctuations - Lass, Michael; Kenter, Tobias; Plessl, Christian; Brehm, Martin (Entropy)
We present a novel approach to characterize and quantify microheterogeneity and microphase separation in computer simulations of complex liquid mixtures. Our post-processing method is based on local density fluctuations of the different constituents in sampling spheres of varying size. It can be easily applied to both molecular dynamics (MD) and Monte Carlo (MC) simulations, including periodic boundary conditions. Multidimensional correlation of the density distributions yields a clear picture of the domain formation due to the subtle balance of different interactions. We apply our approach to the example of force field molecular dynamics simulations of imidazolium-based ionic liquids with different side chain lengths at different temperatures, namely 1-ethyl-3-methylimidazolium chloride, 1-hexyl-3-methylimidazolium chloride, and 1-decyl-3-methylimidazolium chloride, which are known to form distinct liquid domains. We put the results into the context of existing microheterogeneity analyses and demonstrate the advantages and sensitivity of our novel method. Furthermore, we show how to estimate the configuration entropy from our analysis, and we investigate voids in the system. The analysis has been implemented into our program package TRAVIS and is thus available as free software.

Scalable quantum detector tomography by high-performance computing - Schapeler, Timon; Schade, Robert; Lass, Michael; Plessl, Christian; Bartley, Tim (arXiv:2404.02844)
At large scales, quantum systems may become advantageous over their classical counterparts at performing certain tasks. Developing tools to analyse these systems at the relevant scales, in a manner consistent with quantum mechanics, is therefore critical to benchmarking performance and characterising their operation. While classical computational approaches cannot perform like-for-like computations of quantum systems beyond a certain scale, classical high-performance computing (HPC) may nevertheless be useful for precisely these characterisation and certification tasks. By developing open-source customised algorithms using high-performance computing, we perform quantum tomography on a megascale quantum photonic detector covering a Hilbert space of $10^6$. This requires finding $10^8$ elements of the matrix corresponding to the positive operator valued measure (POVM), the quantum description of the detector, and is achieved in minutes of computation time. Moreover, by exploiting the structure of the problem, we achieve highly efficient parallel scaling, paving the way for quantum objects up to a system size of $10^{12}$ elements to be reconstructed using this method. In general, this shows that a consistent quantum mechanical description of quantum phenomena is applicable at everyday scales. More concretely, this enables the reconstruction of large-scale quantum sources, processes and detectors used in computation and sampling tasks, which may be necessary to prove their nonclassical character or quantum computational advantage.

Cold denaturation of DNA origami nanostructures - Dornbusch, Daniel; Hanke, Marcel; Tomm, Emilia; Kielar, Charlotte; Grundmeier, Guido; Keller, Adrian; Fahmy, Karim (Chemical Communications)
The coupling of structural transitions to heat capacity changes leads to destabilization of macromolecules at both, elevated and lowered temperatures. DNA origami not only exhibit this property but also provide...
Keywords: Materials Chemistry; Metals and Alloys; Surfaces; Coatings and Films; General Chemistry; Ceramics and Composites; Electronic; Optical and Magnetic Materials; Catalysis

The association between dairy intake in adolescents with inflammation and risk markers of type 2 diabetes during young adulthood – results of the DONALD study - Hohoff, E; Jankovic, N; Perrar, I; Schnermann, ME; Herder, C; Nöthlings, U; Libuda, Lars; Alexy, U (Public Health Nutrition)
ABSTRACT OBJECTIVE: The aim of this analysis was to investigate whether habitual intake of total dairy (TD) or different dairy types (liquid, solid, fermented, not-fermented, low-fat, high-fat, low-sugar and high-sugar dairy) during adolescence is associated with biomarkers of low-grade inflammation as well as risk factors of type 2 diabetes in young adulthood. DESIGN: Multivariable linear regression analyses were used to investigate prospective associations between estimated TD intake as well as intake of different types of dairy and a pro-inflammatory score, based on hsCRP, IL-6, IL-18, leptin and adiponectin, and insulin resistance assessed as HOMA2-IR in an open cohort study. SETTING: Dortmund, Germany PARTICIPANTS: Data from participants (n=375) of the DOrtmund Nutritional and Anthropometric Longitudinally Designed (DONALD) study were included, for whom at least two 3-day weighed dietary records during adolescence (median age: 11 years) and one blood sample in young adulthood (>18 years) were available. RESULTS: There was no statistically significant association between TD intake or intake of any dairy type and the pro-inflammatory score (all p>0.05). TD intake as well as each dairy type intake and insulin resistance also showed no association (all p>0.05). CONCLUSIONS: The habitual intake of dairy or individual types of dairy during adolescence does not seem to have a major impact on low-grade systemic inflammation and insulin resistance in the long term. There was no indication regarding a restriction of dairy intake for healthy children and adolescents in terms of diabetes risk reduction.
Keywords: Public Health; Environmental and Occupational Health; Nutrition and Dietetics; Medicine (miscellaneous)

Interdisciplinary approaches between physics and art using the example of optical experiments and artistic light installations - Wolke, Nathalie; Laumann, Daniel; Webersen, Yvonne (Physics Education)

Detection and Characterization of Hydride Ligands in Copper Complexes by Hard X‐ray Spectroscopy - Fritsch, Lorena; Rehsies, Pia; Barakat, Wael; Estes, Deven P.; Bauer, Matthias (Chemistry – A European Journal)
Transition metal complexes, particularly copper hydrides, play an important role in various catalytic processes and molecular inorganic chemistry. This study employs synchrotron hard X‐ray spectroscopy to gain insights into the geometric and electronic properties of copper hydrides as potential catalysts for CO2 hydrogenation. The potential of high energy resolution X‐ray absorption near‐edge structure (HERFD‐XANES) and valence‐to‐core X‐ray emission (VtC‐XES) is demonstrated with measurement on Stryker's reagent (Cu6H6) and [Cu3(μ3‐H)(dpmppe)2](PF6)2 (Cu3H), alongside a non‐hydride copper compound (Cu‐I). The XANES analysis reveals that coordination geometries strongly influence the spectra, providing only indirect details about hydride coordination. The VtC‐XES analysis exhibits a distinct signal around 8975 eV, offering a diagnostic tool to identify hydride ligands. Theoretical calculations support and extend these findings by comparing hydride‐containing complexes with their hydride‐free counterparts.

Unbreakable and breakable quantum censorship - Pinske, Julien; Sperling, Jan (Physical Review A)

Reliable electrocortical dynamics of target-directed pass-kicks - Piskin, Daghan Yuksel; Büchel, Daniel; Lehmann, Tim; Baumeister, Jochen (Cognitive Neurodynamics)
Abstract Football is one of the most played sports in the world and kicking with adequate accuracy increases the likelihood of winning a competition. Although studies with different target-directed movements underline the role of distinctive cortical activity on superior accuracy, little is known about cortical dynamics associated with kicking. Mobile electroencephalography is a popular tool to investigate cortical modulations during movement, however, inherent and artefact-related pitfalls may obscure the reliability of functional sources and their activity. The purpose of this study was therefore to describe consistent cortical dynamics underlying target-directed pass-kicks based on test–retest reliability estimates. Eleven participants performed a target-directed kicking task at two different sessions within one week. Electroencephalography was recorded using a 65-channel mobile system and behavioural data were collected including motion range, acceleration and accuracy performance. Functional sources were identified using independent component analysis and clustered in two steps with the components of first and subsequently both sessions. Reliability estimates of event-related spectral perturbations were computed pixel-wise for participants contributing with components of both sessions. The parieto-occipital and frontal clusters were reproducible for the same majority of the sample at both sessions. Their activity showed consistent alpha desyhronization and theta sychnronisation patterns with substantial reliability estimates revealing visual and attentional demands in different phases of kicking. The findings of our study reveal prominent cortical demands during the execution of a target-directed kick which may be considered in practical implementations and provide promising academic prospects in the comprehension and investigation of cortical activity associated with target-directed movements.
Keywords: Exercise Neuroscience

Realization of high-fidelity unitary operations on up to 64 frequency bins - De, Syamsundar; Ansari, Vahid; Sperling, Jan; Barkhofen, Sonja; Brecht, Benjamin; Silberhorn, Christine (Physical Review Research)
The ability to apply user-chosen large-scale unitary operations with high fidelity to a quantum state is key to realizing future photonic quantum technologies. Here, we realize the implementation of programmable unitary operations on up to 64 frequency-bin modes. To benchmark the performance of our system, we probe different quantum walk unitary operations, in particular, Grover walks on four-dimensional hypercubes with similarities exceeding 95% and quantum walks with 400 steps on circles and finite lines with similarities of 98%. Our results open a path toward implementing high-quality unitary operations, which can form the basis for applications in complex tasks, such as Gaussian boson sampling. Published by the American Physical Society 2024

Evaluation of a university seminar on the use of digital media in the physics classroom - Weiler, David; Burde, Jan-Philipp; Große-Heilmann, Rike Isabel; Lachner, Andreas; Riese, Josef; Schubatzky, Thomas (Journal of Physics: Conference Series)
Abstract Fostering digital competencies is an important aspect of pre-service teacher education. However, for physics, there is a lack of systematically surveyed and evidence-based seminars that specifically take into account relevant research findings. Thus, we developed a research-based seminar on the effective use of digital media in physics classrooms and investigated its effects on pre-service teachers (PSTs) professional competencies in a mixed-methods design. Our quantitative analyses of different competence components surveyed in a pre-post-design indicate that the seminar leads to an increase in motivation to use digital media in the physics classroom. Nevertheless, no significant increase in digital-media PCK was found, which could be due to the small sample. The seminar design, however, was predominantly evaluated positively by experts and PSTs in guided interviews. Based on the results, it is planned to further refine the original seminar using a Design-Based Research approach.

Studentisches Gesundheitsmanagement in Deutschland - Ausgangspunkte, Entwicklungen und Status quo - Waltert, Carolin; Kämpfe, Astrid; Steinke, Brigitte (Sport, Bewegung und Gesundheit in internationaler Perspektive. Festschrift zur Verabscheidung von Prof. Dr. Hans Peter Brndl-Bredenbeck)

Duale Karrieren: Chronischer Stress und protektive Ressourcen - Längsschnittstudien im Vergleich zweier Verbundsysteme - Breithecker, Jennifer; Kehne, Miriam (Sport, Bewegung und Gesundheit in internationaler Perspektive. Festschrift zur Verabscheidung von Prof. Dr. Hans Peter Brndl-Bredenbeck)

Forschungsstand zu Bewegung, Spiel und Sport im schulischen Ganztag in Deutschland: ein Scoping Review - Noetzel, Ida; Becker, Linda; Gräfin v. Plettenberg, Elisabeth; Kehne, Miriam (Forum Kinder- und Jugendsport)
Die Studienlage zum Thema Bewegung, Spiel und Sport im schulischen Ganztag in Deutschland zeigt sich vielseitig. Das Forschungsfeld ist neben wenigen umfassenden, überregionalen Studien durch kleinere Studien mit spezifischen inhaltlichen Schwerpunkten gekennzeichnet. Das vorliegende Scoping Review zielt darauf ab, die Erkenntnisse des Forschungsfeldes der circa vergangenen 20 Jahre zu systematisieren. Leitend ist die Forschungsfrage „Wie stellt sich der aktuelle Forschungsstand im Feld von Bewegung, Spiel und Sport im schulischen Ganztag in Deutschland dar?“ Auf Basis einer systematischen Literaturrecherche in fünf Datenbanken konnten aus 2365 Publikationen 52 in die Analyse eingeschlossen werden. Überwiegend wurden regionale Querschnittsstudien mit spezifischem Fokus durchgeführt. Die Studien befassen sich zumeist mit den Rahmenbedingungen von Bewegung, Spiel und Sport im Ganztag sowie mit den Charakteristika von Bewegung, Spiel und Sport im Ganztag. Die Analyse verdeutlicht unter anderem den Mangel an längsschnittlichen Studien sowie den Forschungsbedarf im Bereich der Qualität von Bewegung in diesem Setting.
Keywords: Review; Ganztag; Bewegung; Spiel; Sport; Forschungsstand

Natural near field coupled leaky-mode resonant anti-reflection structures: the setae of Cataglyphis bombycina - Schwind, Bertram; Wu, Xia; Tiemann, Michael; Fabritius, Helge-Otto (Frontiers in Physics)
Leaky mode resonances of the setae of Cataglyphis bombycina are found to enhance the thermal emission of the animals by near field coupling to the chitinous exoskeleton. This is remarkable, as the setae are also an adaption to enhance the reflectivity in the visible wavelength range. Both effects are dependent on morphology, dimensions and spatial arrangement. These parameters were experimentally characterized and simulated by finite difference time domain simulations to elucidate the optical impact of the setae in the mid infrared range and the contribution of leaky mode resonances. This mode of action and the setae’s optical properties in the visible range explain evolutionary strains that led to the actual morphology and size of the setae.

The acute effect of a β-glucan-enriched oat bread on gastric emptying, GLP-1 response, and postprandial glycaemia and insulinemia: a randomised crossover trial in healthy adults - Revheim, Ingrid; Ballance, Simon; Standal, Adelheid Fretland; Rieder, Anne; Dierkes, Jutta; Buyken, Anette; Gilja, Odd Helge; Hausken, Trygve; Rosendahl-Riise, Hanne (Nutrition & Metabolism)
Abstract Background The cereal fibre β-glucan reduces postprandial glycaemia, however, the underlying mechanisms are not fully understood. Thus, the aim of this study was to investigate the acute effect of a β-glucan-enriched oat bread on gastric emptying half-time ( T 1/2 ), gastric emptying lag phase ( T lag ), and gastric emptying rate (GER), and the secretion of glucagon-like peptide-1 (GLP-1) as potential means to influence postprandial glycaemia. Methods A randomised crossover trial was conducted in 22 healthy adults (age 24.6 ± 3.1 years, BMI 23.1 ± 2.7 kg/m 2 ) receiving 25 g available carbohydrates from a β-glucan-enriched oat bread or a control whole-wheat bread at two non-consecutive days. T 1/2 , T lag , and GER were determined based on ultrasound measures of the cross-sectional gastric antrum area in the fasting state and 15, 30, 45, 60, 90, and 120 min postprandially. Capillary glucose, serum insulin, and plasma GLP-1 concentrations were measured at the same time points. Results A biphasic pattern of gastric emptying with a distinct T lag before the commencement of emptying was observed in most subjects for both bread types. While no differences in GER were evident ( p = 0.562), consumption of the oat bread significantly increased T 1/2 by 18 min and T lag by 14 min compared with the whole-wheat bread ( p = 0.005 and p = 0.010, respectively). In addition, the oat bread significantly reduced iAUC 2h for glucose and insulin responses compared with the whole-wheat bread ( p = 0.001 and p < 0.001, respectively). There were no significant differences in GLP-1 response between the two breads ( p = 0.892). Conclusion The increased T 1/2 and T lag could offer a potential mechanism for the observed attenuation of postprandial glycaemia and insulinemia after consumption of the β-glucan-enriched oat bread compared with the whole-wheat bread. Trial registration : The study is registered at clinicaltrails.gov (NCT04571866).

Protein intake and cancer: an umbrella review of systematic reviews for the evidence-based guideline of the German Nutrition Society - Kühn, Tilman; Kalotai, Nicole; Amini, Anna M.; Haardt, Julia; Lehmann, Andreas; Schmidt, Annemarie; Buyken, Anette; Egert, Sarah; Ellinger, Sabine; Kroke, Anja; Lorkowski, Stefan; Louis, Sandrine; et al. (European Journal of Nutrition)
Abstract Purpose It has been proposed that a higher habitual protein intake may increase cancer risk, possibly via upregulated insulin-like growth factor signalling. Since a systematic evaluation of human studies on protein intake and cancer risk based on a standardised assessment of systematic reviews (SRs) is lacking, we carried out an umbrella review of SRs on protein intake in relation to risks of different types of cancer. Methods Following a pre-specified protocol (PROSPERO: CRD42018082395), we retrieved SRs on protein intake and cancer risk published before January 22th 2024, and assessed the methodological quality and outcome-specific certainty of the evidence using a modified version of AMSTAR 2 and NutriGrade, respectively. The overall certainty of evidence was rated according to predefined criteria. Results Ten SRs were identified, of which eight included meta-analyses. Higher total protein intake was not associated with risks of breast, prostate, colorectal, ovarian, or pancreatic cancer incidence. The methodological quality of the included SRs ranged from critically low (kidney cancer), low (pancreatic, ovarian and prostate cancer) and moderate (breast and prostate cancer) to high (colorectal cancer). The outcome-specific certainty of the evidence underlying the reported findings on protein intake and cancer risk ranged from very low (pancreatic, ovarian and prostate cancer) to low (colorectal, ovarian, prostate, and breast cancer). Animal and plant protein intakes were not associated with cancer risks either at a low (breast and prostate cancer) or very low (pancreatic and prostate cancer) outcome-specific certainty of the evidence. Overall, the evidence for the lack of an association between protein intake and (i) colorectal cancer risk and (ii) breast cancer risk was rated as possible . By contrast, the evidence underlying the other reported results was rated as insufficient . Conclusion The present findings suggest that higher total protein intake may not be associated with the risk of colorectal and breast cancer, while conclusions on protein intake in relation to risks of other types of cancer are restricted due to insufficient evidence.

Dietary protein and blood pressure: an umbrella review of systematic reviews and evaluation of the evidence - Boeing, Heiner; Amini, Anna M.; Haardt, Julia; Schmidt, Annemarie; Bischoff-Ferrari, Heike A.; Buyken, Anette; Egert, Sarah; Ellinger, Sabine; Kroke, Anja; Lorkowski, Stefan; Louis, Sandrine; Nimptsch, Katharina; et al. (European Journal of Nutrition)
Abstract Introduction This umbrella review aimed to investigate the evidence of an effect of dietary intake of total protein, animal and plant protein on blood pressure (BP), and hypertension (PROSPERO: CRD42018082395). Methods PubMed, Embase and Cochrane Database were systematically searched for systematic reviews (SRs) of prospective studies with or without meta-analysis published between 05/2007 and 10/2022. The methodological quality and outcome-specific certainty of evidence were assessed by the AMSTAR 2 and NutriGrade tools, followed by an assessment of the overall certainty of evidence. SRs investigating specific protein sources are described in this review, but not included in the assessment of the overall certainty of evidence. Results Sixteen SRs were considered eligible for the umbrella review. Ten of the SRs investigated total protein intake, six animal protein, six plant protein and four animal vs. plant protein. The majority of the SRs reported no associations or effects of total, animal and plant protein on BP (all “possible” evidence), whereby the uncertainty regarding the effects on BP was particularly high for plant protein. Two SRs addressing milk-derived protein showed a reduction in BP; in contrast, SRs investigating soy protein found no effect on BP. The outcome-specific certainty of evidence of the SRs was mostly rated as low. Discussion/conclusion This umbrella review showed uncertainties whether there are any effects on BP from the intake of total protein, or animal or plant proteins, specifically. Based on data from two SRs with milk protein, it cannot be excluded that certain types of protein could favourably influence BP.

Glycemic response to meals with a high glycemic index differs between morning and evening: a randomized cross-over controlled trial among students with early or late chronotype - Stutz, Bianca; Krueger, Bettina; Goletzke, Janina; Jankovic, Nicole; Alexy, Ute; Herder, Christian; Dierkes, Jutta; Berg-Beckhoff, Gabriele; Jakobsmeyer, Rasmus; Reinsberger, Claus; Buyken, Anette (European Journal of Nutrition)
Abstract Purpose Glycemic response to the same meal depends on daytime and alignment of consumption with the inner clock, which has not been examined by individual chronotype yet. This study examined whether the 2-h postprandial and 24-h glycemic response to a meal with high glycemic index (GI) differ when consumed early or late in the day among students with early or late chronotype. Methods From a screening of 327 students aged 18–25 years, those with early (n = 22) or late (n = 23) chronotype participated in a 7-day randomized controlled cross-over intervention study. After a 3-day observational phase, standardized meals were provided on run-in/washout (days 4 and 6) and intervention (days 5 and 7), on which participants received a high GI meal (GI = 72) in the morning (7 a.m.) or in the evening (8 p.m.). All other meals had a medium GI. Continuous glucose monitoring was used to measure 2-h postprandial and 24-h glycemic responses and their variability. Results Among students with early chronotype 2-h postprandial glucose responses to the high GI meal were higher in the evening than in the morning (iAUC: 234 (± 92) vs. 195 (± 91) (mmol/L) × min, p = 0.042). Likewise, mean and lowest 2-h postprandial glucose values were higher when the high GI meal was consumed in the evening (p < 0.001; p = 0.017). 24-h glycemic responses were similar irrespective of meal time. Participants with late chronotype consuming a high GI meal in the morning or evening showed similar 2-h postprandial (iAUC: 211 (± 110) vs. 207 (± 95) (mmol/L) × min, p = 0.9) and 24-h glycemic responses at both daytimes. Conclusions Diurnal differences in response to a high GI meal are confined to those young adults with early chronotype, whilst those with a late chronotype seem vulnerable to both very early and late high GI meals. Registered at clinicaltrials.gov (NCT04298645; 22/01/2020).

Nutri-Score 2023 update - Merz, Benedikt; Temme, Elisabeth; Alexiou, Hélène; Beulens, Joline Wilhelma Johanna; Buyken, Anette; Bohn, Torsten; Ducrot, Pauline; Falquet, Marie-Noëlle; Solano, Marta García; Haidar, Hanna; Infanger, Esther; Kühnelt, Charlotte; et al. (Nature Food)

The Mode of Endurance Exercise Influences Changes in EEG Resting State Graphs among High-Level Cross-Country Skiers - Büchel, Daniel; Torvik, Per Øyvind; Lehmann, Tim; Sandbakk, Øyvind; Baumeister, Jochen (Medicine & Science in Sports & Exercise)
Keywords: Physical Therapy; Sports Therapy and Rehabilitation; Orthopedics and Sports Medicine

Stimuli‐accelerated polymeric drug delivery systems - Rust, Tarik; Jung, Dimitri; Langer, Klaus; Kuckling, Dirk (Polymer International)
The controlled delivery of active pharmaceutical ingredients to the site of disease represents a major challenge in drug therapy. Particularly when drugs have to be transported across biological barriers, suitable drug delivery systems are of importance. In recent years responsive delivery systems have been developed which enable a controlled drug release depending on internal or external stimuli such as changes in pH, redox environment or light and temperature. In some studies delivery systems with reactivity against two different stimuli were established either to enhance the response by synergies of the stimuli or to broaden the window of possible trigger events. In the present review numerous exciting developments of pH-, light- and redox-cleavable polymers suitable for the preparation of smart delivery systems are described. The review discusses the different stimuli that can be used for a controlled drug release of polymer-based delivery systems. It puts a focus on the different polymers described for the preparation of stimuli-sensitive systems, their preparation techniques as well as their stimuli-responsive degradation. © 2022 The Authors. Polymer International published by John Wiley & Sons Ltd on behalf of Society of Industrial Chemistry.
Keywords: drug delivery system; stimuli; polymer; cleavable

Zu unangenehm, zu viel Aufwand oder keine Möglichkeit? – Emotionen und Bereitschaft von Lehramtsstudierenden zur Videografie eigenen Unterrichts - Vogelsang, Christoph; Pollmeier, Pascal; Gockeln, Theresa; Rogge, Tim (Zeitschrift für Bildungsforschung)
Videografien eigenen Unterrichts sind ein mögliches methodisches Werkzeug zur Förderung der professionellen Kompetenz angehender Lehrkräfte, das allerdings innerhalb der Lehramtsausbildung noch nicht breit implementiert ist. Ein möglicher Grund hierfür könnte neben organisatorischen Herausforderungen auch in einer geringen Akzeptanz von Eigenvideografien durch Lehramtsstudierende liegen. Um besser abschätzen zu können, mit welchen Voraussetzungen affektiv-emotionaler Art bei einer breiteren Implementierung im Lehramtsstudium gerechnet werden kann, wurden N = 938 Lehramtsstudierende im Masterstudium an der Universität Paderborn zu ihren Emotionen und Bereitschaften zur Arbeit mit Eigenvideografien befragt. Dabei wurde auch erfasst, wie sich diese je nach bestehenden Erfahrungen zur Arbeit mit Videografien unterscheiden. In den Ergebnissen zeigen sich kaum affektiv-emotionale Reaktionen zur Eigenvideografie, und wenn, vor allem Gefühle der Unsicherheit. Zu beachten ist, dass zwar bei gut der Hälfte der Studierenden eine eher hohe generelle Bereitschaft zur Eigenvideografie besteht, eine konkrete Intention bzw. eine konkrete Volition zur Videografie aber geringer ist. Die ca. 10 % der Studierenden mit Eigenvideografieerfahrung im Studium zeigen erwartungsgemäß höhere Bereitschaften, aber unerwartet keine signifikant positiveren Emotionen. Insgesamt verdeutlichen die Ergebnisse, dass bzgl. der Akzeptanz der Studierenden ein höheres Potenzial zur Implementation von Eigenvideografien im Studium vorliegt, als aktuell ausgeschöpft wird.
Keywords: Lehrerbildung; Videografie; Praxissemester; Emotionen; Akzeptanz

Nanosecond gating of superconducting nanowire single-photon detectors using cryogenic bias circuitry - Hummel, Thomas; Widhalm, Alex; Höpker, Jan Philipp; Jöns, Klaus; Chang, Jin; Fognini, Andreas; Steinhauer, Stephan; Zwiller, Val; Zrenner, Artur; Bartley, Tim (Optics Express)
Superconducting nanowire single-photon detectors (SNSPDs) show near unity efficiency, low dark count rate, and short recovery time. Combining these characteristics with temporal control of SNSPDs broadens their applications as in active de-latching for higher dynamic range counting or temporal filtering for pump-probe spectroscopy or LiDAR. To that end, we demonstrate active gating of an SNSPD with a minimum off-to-on rise time of 2.4 ns and a total gate length of 5.0 ns. We show how the rise time depends on the inductance of the detector in combination with the control electronics. The gate window is demonstrated to be fully and freely, electrically tunable up to 500 ns at a repetition rate of 1.0 MHz, as well as ungated, free-running operation. Control electronics to generate the gating are mounted on the 2.3 K stage of a closed-cycle sorption cryostat, while the detector is operated on the cold stage at 0.8 K. We show that the efficiency and timing jitter of the detector is not altered during the on-time of the gating window. We exploit gated operation to demonstrate a method to increase in the photon counting dynamic range by a factor 11.2, as well as temporal filtering of a strong pump in an emulated pump-probe experiment.
Keywords: Atomic and Molecular Physics; and Optics

Associations of chronotype and social jetlag with eating jetlag and their changes among German students during the first COVID-19 lockdown. The Chronotype and Nutrition study. - Stutz, Bianca; Buyken, Anette E.; Schadow, Alena; Jankovic, N; Alexy, U; Krueger, Betina (Appetite)

Dynamics of DNA Origami Lattices - Julin, Sofia; Keller, Adrian; Linko, Veikko (Bioconjugate Chemistry)
Keywords: Organic Chemistry; Pharmaceutical Science; Pharmacology; Biomedical Engineering; Bioengineering; Biotechnology

Does Augmented Reality Help to Understand Chemical Phenomena during Hands-On Experiments?–Implications for Cognitive Load and Learning - Peeters, Hendrik; Habig, Sebastian; Fechner, Sabine (Multimodal Technologies and Interaction)
Chemical phenomena are only observable on a macroscopic level, whereas they are explained by entities on a non-visible level. Students often demonstrate limited ability to link these different levels. Augmented reality (AR) offers the possibility to increase contiguity by embedding virtual models into hands-on experiments. Therefore, this paper presents a pre- and post-test study investigating how learning and cognitive load are influenced by AR during hands-on experiments. Three comparison groups (AR, animation and filmstrip), with a total of N = 104 German secondary school students, conducted and explained two hands-on experiments. Whereas the AR group was allowed to use an AR app showing virtual models of the processes on the submicroscopic level during the experiments, the two other groups were provided with the same dynamic or static models after experimenting. Results indicate no significant learning gain for the AR group in contrast to the two other groups. The perceived intrinsic cognitive load was higher for the AR group in both experiments as well as the extraneous load in the second experiment. It can be concluded that AR could not unleash its theoretically derived potential in the present study.
Keywords: augmented reality; chemistry education; models; experiment; cognitive load

Effekte des Feedbacks von Lehrkräften auf die Selbstwirksamkeitsüberzeugungen und die intrinsische Motivation von Kindern im naturwissenschaftlichen Sachunterricht der Grundschule. Vortrag auf der 10. Tagung der Gesellschaft für Empirische Bildungsforschung (GEBF). Thema: „Bildung zwischen Unsicherheit und Evidenz“ - Hoya, Fabian Karl; Schulze, Jan Roland; Blumberg, Eva; Hellmich, Frank

Experimentelle Kompetenz Physikstudierender - Bauer, Anna Brigitte
Für den Erwerb fachmethodischer Fähigkeiten stellen Laborpraktika eine zentrale Lerngelegenheiten des Physikstudiums dar. Trotz ihrer hohen Bedeutung fehlt ein hochschulfachdidaktischer Diskurs zu einer lehr-lerntheoretischen Fundierung. Zudem wird ihre Lernwirksamkeit aufgrund der bestehenden didaktischen Gestaltung kritisiert. Die weit verbreiteten engmaschigen Aufgabenstellungen enthalten keine Anreize zur tiefergehenden Auseinandersetzung mit den Inhalten. Um der Diskrepanz zwischen den Zielsetzungen und den von den Lernenden erworbenen Fähigkeiten entgegenzuwirken, liegen aktuell nur wenige und zudem nur punktuelle Grundlagen für eine evidenzbasierte Überarbeitung dieses Veranstaltungsformates vor. Ziel dieser Arbeit ist daher, einen Vorschlag für ein performanzorientiertes Kompetenzstrukturmodell auf universitärem Niveau zu entwickeln, das die Inhaltsbereiche, die experimentellen Fähigkeiten und Fertigkeiten sowie die Qualitätsausprägungen experimenteller Handlungen systematisiert.Die Modellierung ist auf Basis der Analyse videografierter experimenteller Performanz von 16 unterschiedlich fähigen Proband:innen realisiert worden. Für die Entwicklung der Dimensionen Fachmethodik und Qualitätsausprägung werden unter Nutzung der qualitativen Forschungsansätze Dokumentarische Methode und Typenbildung die charakteristischen Merkmale universitären Experimentierens identifiziert und anschließend systematisiert. Zur Prüfung der Passung des Modells zur Perspektive der Wissenschaft Physik ist ein Interrating mit einem Fachwissenschaftler durchgeführt worden, das sehr gute Übereinstimmungswerte liefert. Die Passung des Modells zur Perspektive der Praktikumsleiter:innen ist durch ein Expertenrating erfolgt. Ein Rangfolgen-Vergleich zeigt hohe Übereinstimmungswerte.

The association of chronotype and social jet lag with body composition in German students: The role of physical activity behaviour and the impact of the pandemic lockdown - Krueger, Betina; Stutz, Bianca; Jankovic, Nicole; Alexy, Ute; Kilanowski, Anna; Libuda, Lars; Buyken, Anette E. (PLOS ONE)
Young adults with a later chronotype are vulnerable for a discrepancy in sleep rhythm between work- and free days, called social jet lag (SJL). This study analysed (i) chronotype/SJL association with visceral fat/skeletal muscle mass, (ii) the attribution to physical activity behaviour, and (iii) chronotype-specific changes in physical activity behaviour in young adults during the Covid-19 pandemic lockdown. Chronotype and SJL were derived from the Munich-Chrono-Type-Questionnaire in 320 German students (age 18–25 years) from September 2019 to January 2020, 156 of these participated in an online follow-up survey in June 2020. Body composition was assessed by bioimpedance analysis at baseline. Multivariable linear regression analyses were used to relate chronotype/SJL to body composition; the contribution of self-reported physical activity was tested by mediation analysis. At baseline, a later chronotype and a larger SJL were associated with a higher visceral fat mass (P<0.05), this relation was notably mediated by the attention to physical activity (P<0.05). Chronotype (P = 0.02) but not SJL (P = 0.87) was inversely associated with skeletal muscle mass. During the pandemic lockdown, chronotype hardly changed, but SJL was reduced. Timing and physical activity behaviour remained in most participants and changes were unrelated to chronotype (all P>0.07). A later chronotype/higher SJL may increase the risk of a higher visceral fat mass even in this relatively healthy sample, which may be partly due to their physical activity behaviour. Despite a reduction in SJL during the pandemic lockdown, later chronotypes did not change their physical activity behaviour more than earlier chronotypes.
Keywords: Multidisciplinary

Including: Thinking Towards an Inclusive Curriculum for Technology Education in German Primary Schools - Schröer, Franz; Tenberge, Claudia (Bloomsbury Handbook of Technology Education)
Keywords: Curriculum; Inclusion; Sachunterricht; Participation

Technology education in elementary school using the example of 'learning robots' – development and evaluation of an in-service teacher training concept - Janicki, Nicole; Tenberge, Claudia (Australasian Journal of Technology Education)
Keywords: technology education; teacher professionalisation; Computational Thinking; digitalization; learning robots

Lehre in Zeiten von Digitalisierung und Inklusion – Beispiele aus drei Fächern. - Schmidt, Rebekka; Tenberge, Claudia; Häsel-Weide, Uta

Reusability of Germany´s total diet study food list upon availability of new food consumption data—comparison of three update strategies - Kolbaum, Anna Elena; Ptok, Sebastian; Jung, Christian; Libuda, Lars; Lindtner, Oliver (Journal of Exposure Science & Environmental Epidemiology)
Abstract Background The German total diet study (TDS)—BfR MEAL Study—established its food list in 2016 based on food consumption data of children (0.5–<5 years) and adults (14–80 years). The list consists of 356 foods selected for analysis in order to ensure ≥90% coverage of the diet. Recently, new food consumption data for children (0.5–<6 and 6–<12 years) in Germany became available, which raised the opportunity to evaluate the applicability of the MEAL food list 2016 on new data. Objective We tested the hypotheses that the MEAL food list 2016 also covers ≥90% of the diet of the new collected food consumption data, and that the selection of foods from younger children and adults was sufficient to also cover the middle age group (6–<12 years). Strategies for updating the existing food list were assessed. Methods Three approaches evaluated the reusability and potential adjustment strategies of the existing food list. Approach 1 applied the existing food list to new food consumption data. Approach 2 allowed the extension of the existing food list to improve coverage of food consumption. Approach 3 set up a new food list based on the new data. Results The MEAL food list 2016 covered 94% of the overall diet of the new collected food consumption data. The diet of the middle age group was sufficiently covered with 91%. However, coverage on main food group or population subgroup level was <90% in some cases. Approach 3 most accurately identified relevant modifications to the existing food list. 94% of the MEAL food list 2016 could be re-used and 51 new foods were identified as potentially relevant. Significance The results suggest that a high investment in the coverage of a TDS food list will lower the effort and the resources to keep data updated in the long-term. Impact There is no established approach to update a TDS food list. This study provides comparative approaches to handle newly collected food consumption data for follow-on TDS activities. The results provide useful information for institutions planning or updating a TDS. Furthermore, new food consumption data for children in Germany recently became available and are here presented for the first time.
Keywords: Public Health; Environmental and Occupational Health; Pollution; Toxicology; Epidemiology

Nonlinear Dielectric Nanoresonators and Metasurfaces: Toward Efficient Generation of Entangled Photons - Sharapova, Polina R.; Kruk, Sergey S.; Solntsev, Alexander S. (Laser & Photonics Reviews)
Keywords: Condensed Matter Physics; Atomic and Molecular Physics; and Optics; Electronic; Optical and Magnetic Materials

Coherent Quantum Interconnection between On-Demand Quantum Dot Single Photons and a Resonant Atomic Quantum Memory - Cui, Guo-Dong; Schweickert, Lucas; Jöns, Klaus D.; Namazi, Mehdi; Lettner, Thomas; Zeuner, Katharina D.; Montaña, Lara Scavuzzo; Silva, Saimon Filipe Covre da; Reindl, Marcus; Huang, Huiying; Trotta, Rinaldo; Rastelli, Armando; et al. (arXiv:2301.10326)
Long-range quantum communication requires the development of in-out light-matter interfaces to achieve a quantum advantage in entanglement distribution. Ideally, these quantum interconnections should be as fast as possible to achieve high-rate entangled qubits distribution. Here, we demonstrate the coherent quanta exchange between single photons generated on-demand from a GaAs quantum dot and atomic ensemble in a $^{87}$Rb vapor quantum memory. Through an open quantum system analysis, we demonstrate the mapping between the quantized electric field of photons and the coherence of the atomic ensemble. Our results play a pivotal role in understanding quantum light-matter interactions at the short time scales required to build fast hybrid quantum networks.

Cortical thickness and neurocognitive performance in former high‐level female soccer and non‐contact sport athletes - Haase, Franziska Katharina; Prien, Annika; Douw, Linda; Feddermann‐Demont, Nina; Junge, Astrid; Reinsberger, Claus (Scandinavian Journal of Medicine & Science in Sports)
Keywords: Physical Therapy; Sports Therapy and Rehabilitation; Orthopedics and Sports Medicine

Tailored Frequency Conversion Makes Infrared Light Visible for Streak Cameras - Lüders, Carolin; Gil-Lopez, Jano; Allgaier, Markus; Brecht, Benjamin; Aßmann, Marc; Silberhorn, Christine; Bayer, Manfred (Physical Review Applied)
Keywords: General Physics and Astronomy

Circularly Polarized Lasing from a Microcavity Filled with Achiral Single‐Crystalline Microribbons - Liang, Qian; Ma, Xuekai; Long, Teng; Yao, Jiannian; Liao, Qing; Fu, Hongbing (Angewandte Chemie International Edition)
Keywords: General Chemistry; Catalysis

Dynamic conditioning of two particle discrete-time quantum walks - Pegoraro, Federico; Held, Philip; Barkhofen, Sonja; Brecht, Benjamin; Silberhorn, Christine (Physica Scripta)
In real photonic quantum systems losses are an unavoidable factor limiting the scalability to many modes and particles, restraining their application in fields as quantum information and communication. For this reason, a considerable amount of engineering effort has been taken in order to improve the quality of particle sources and system components. At the same time, data analysis and collection methods based on post-selection have been used to mitigate the effect of particle losses. This has allowed for investigating experimentally multi-particle evolutions where the observer lacks knowledge about the system's intermediate propagation states. Nonetheless, the fundamental question how losses affect the behaviour of the surviving subset of a multi-particle system has not been investigated so far. For this reason, here we study the impact of particle losses in a quantum walk of two photons reconstructing the output probability distributions for one photon conditioned on the loss of the other in a known mode and temporal step of our evolution network. We present the underlying theoretical scheme that we have devised in order to model controlled particle losses, we describe an experimental platform capable of implementing our theory in a time multiplexing encoding. In the end we show how localized particle losses change the output distributions without altering their asymptotic spreading properties. Finally we devise a quantum civilization problem, a two walker generalisation of single particle recurrence processes.

Weaker Quadriceps Corticomuscular Coherence in Individuals Following ACL Reconstruction during Force Tracing - Sherman, David A.; Baumeister, Jochen; Stock, Matt S.; Murray, Amanda M.; Bazett-Jones, David M.; Norte, Grant E. (Medicine & Science in Sports & Exercise)
Keywords: Physical Therapy; Sports Therapy and Rehabilitation; Orthopedics and Sports Medicine

The Mode of Endurance Exercise Influences Changes in EEG Resting State Graphs among High-Level Cross-Country Skiers. - Büchel, Daniel; Torvik, PØ; Lehmann, Tim; Sandbakk, Ø; Baumeister, Jochen (Med Sci Sports Exerc)

Inhibition of Motor Planning and Response Selection after Anterior Cruciate Ligament Reconstruction. - Sherman, DA; Baumeister, Jochen; Stock, MS; Murray, AM; Bazett-Jones, DM; Norte, GE (Med Sci Sports Exerc)

Characterizing Ion Transport in Electrolytes via Concentration and Velocity Profiles - Mistry, Aashutosh; Srinivasan, Venkat; Steinrück, Hans-Georg (Advanced Energy Materials)
Keywords: General Materials Science; Renewable Energy; Sustainability and the Environment

Three-dimensional dipole momentum analog based on L-shape metasurface - Li, Tianyou; Chen, Yanjie; Wang, Yongtian; Zentgraf, Thomas; Huang, Lingling (Applied Physics Letters)
The achievement of a flat metasurface has realized extraordinary control over light–matter interaction at the nanoscale, enabling widespread use in imaging, holography, and biophotonics. However, three-dimensional metasurfaces with the potential to provide additional light–matter manipulation flexibility attract only little interest. Here, we demonstrate a three-dimensional metasurface scheme capable of providing dual phase control through out-of-plane plasmonic resonance of L-shape antennas. Under circularly polarized excitation at a specific wavelength, the L-shape antennas with rotating orientation angle act as spatially variant three-dimensional tilted dipoles and are able to generate desire phase delay for different polarization components. Generalized Snell's law is achieved for both in-plane and out-of-plane dipole components through arranging such L-shape antennas into arrays. These three-dimensional metasurfaces suggest a route for wavefront modulation and a variety of nanophotonic applications.
Keywords: Physics and Astronomy (miscellaneous)

Room-Temperature Electrical Field-Enhanced Ultrafast Switch in Organic Microcavity Polariton Condensates - De, Jianbo; Ma, Xuekai; Yin, Fan; Ren, Jiahuan; Yao, Jiannian; Schumacher, Stefan; Liao, Qing; Fu, Hongbing; Malpuech, Guillaume; Solnyshkov, Dmitry (Journal of the American Chemical Society (JACS))
Keywords: Colloid and Surface Chemistry; Biochemistry; General Chemistry; Catalysis

Circularly polarized electroluminescence from a single-crystal organic microcavity light-emitting diode based on photonic spin-orbit interactions - Jia, Jichao; Cao, Xue; Ma, Xuekai; De, Jianbo; Yao, Jiannian; Schumacher, Stefan; Liao, Qing; Fu, Hongbing (Nature Communications)
Keywords: General Physics and Astronomy; General Biochemistry; Genetics and Molecular Biology; General Chemistry; Multidisciplinary

Quantum-optical excitations of semiconductor nanostructures in a microcavity using a two-band model and a single-mode quantum field - Rose, Hendrik; Vasil'ev, A. N.; Tikhonova, O. V.; Meier, Torsten; Sharapova, Polina (Physical Review A)

Boron‐Centered Lewis Superacid through Redox‐Active Ligands: Application in C−F and S−F Bond Activation - Köring, Laura; Stepen, Arne; Birenheide, Bernhard; Barth, Simon; Leskov, Maxim; Schoch, Roland; Krämer, Felix; Breher, Frank; Paradies, Jan (Angewandte Chemie International Edition)
Keywords: General Chemistry; Catalysis

Boron‐Centered Lewis Superacid through Redox‐Active Ligands: Application in C−F and S−F Bond Activation - Köring, Laura; Stepen, Arne; Birenheide, Bernhard; Barth, Simon; Leskov, Maxim; Schoch, Roland; Krämer, Felix; Breher, Frank; Paradies, Jan (Angewandte Chemie)
Keywords: General Medicine

Developing Quantitative Nondestructive Characterization of Nanomaterials: A Case Study on Sequential Infiltration Synthesis of Block Copolymers - Cara, Eleonora; Hönicke, Philipp; Kayser, Yves; Lindner, Jörg K. N.; Castellino, Micaela; Murataj, Irdi; Porro, Samuele; Angelini, Angelo; De Leo, Natascia; Pirri, Candido Fabrizio; Beckhoff, Burkhard; Boarino, Luca; et al. (ACS Applied Polymer Materials)
Keywords: Organic Chemistry; Polymers and Plastics; Process Chemistry and Technology

Realization of a Multi-Output Quantum Pulse Gate for Decoding High-Dimensional Temporal Modes of Single-Photon States - Serino, Laura; Gil López, Jano; Stefszky, Michael; Ricken, Raimund; Eigner, Christof; Brecht, Benjamin; Silberhorn, Christine (PRX Quantum)
Keywords: General Physics and Astronomy; Mathematical Physics; Applied Mathematics; Electronic; Optical and Magnetic Materials; Electrical and Electronic Engineering; General Computer Science

Experimental studies of the excitonic nonlinear response of GaAs-based type-I and type-II quantum well structures interacting with optical and terahertz fields - Meier, Torsten; Stein, M.; Schäfer, F.; Anders, D.; Littmann, J. H.; Fey, M.; Trautmann, Alexander; Ngo, C.; Steiner, J. T.; Reichelt, Matthias; Fuchs, C.; Volz, K.; et al. (Ultrafast Phenomena and Nanophotonics XXVII)
The nonlinear optical response of quantum well excitons is investigated experimentally using polarization resolved four wave mixing, optical-pump optical-probe, and optical-pump Terahertz-probe spectroscopy. The four-wave mixing data reveal clear signatures of coherent biexcitons which concur with straight-forward polarization selection rules at the Γ point. The type-I samples show the well-established time-domain beating signatures in the transients as well as the corresponding spectral signatures clearly. The latter are also present in type-II samples; however, the smaller exciton and biexciton binding energies in these structures infer longer beating times which, in turn, are accompanied by faster dephasing of the type-II exciton coherences. Furthermore, the THz absorption following spectrally narrow, picosecond excitation at energies in the vicinity of the 1s exciton resonance are discussed. Here, the optical signatures yield the well-established redshifts and blueshifts for the appropriate polarization geometries in type-I quantum well samples also termed “AC Stark Effect”. The THz probe reveals intriguing spectral features which can be ascribed to coherent negative absorption following an excitation into a virtual state for an excitation below the 1s exciton resonance. Furthermore, the scattering and ionization of excitons is discussed for several excitation geometries yielding control rules for elastic and inelastic quasiparticle collisions.

Terahertz-induced anomalous currents following the optical excitation of excitons in semiconductor quantum wells - Meier, Torsten; Ngo, C.; Priyadarshi, S.; Duc, H. T.; Bieler, M. (Ultrafast Phenomena and Nanophotonics XXVII)
Anomalous currents refer to electronic currents that flow perpendicularly to the direction of the accelerating electric field. Such anomalous currents can be generated when Terahertz fields are applied after an optical interband excitation of GaAs quantum wells. The underlying processes are investigated by numerical solutions of the semiconductor Bloch equations in the length gauge. Excitonic effects are included by treating the manybody Coulomb interaction in time-dependent Hartree-Fock approximation and additionally also carrier-phonon scattering processes are considered. The band structure and matrix elements are obtained from a 14-band k · p model within the envelope function approximation. The random phase factors of the matrix elements that appear due to the separate numerical diagonalization at each k-point are treated by applying a smooth gauge transformation. We present the macroscopic Berry curvature and anomalous current transients with and without excitonic effects. It is demonstrated that the resonant optical excitation of excitonic resonances can significantly enhance the Berry curvature and the anomalous currents.

Analysis of the nonlinear optical response of excitons in type-I and type-II quantum wells including many-body correlations - Meier, Torsten; Trautmann, Alexander; Stein, M.; Schäfer, F.; Anders, D.; Ngo, C.; Steiner, J. T.; Reichelt, Matthias; Chatterjee, S. (Ultrafast Phenomena and Nanophotonics XXVII)
The nonlinear optical response of quantum well excitons excited by optical fields is analyzed by numerical solutions of the semiconductor Bloch equations. Differential absorption spectra are computed for resonant pumping at the exciton resonance and the dependence of the absorption changes on the polarization directions of the pump and probe pulses is investigated. Coherent biexcitonic many-body correlations are included in our approach up to third-order in the optical fields. Results are presented for spatially-direct type-I and spatiallyindirect type-II quantum well systems. Due to the spatial inhomogeneity, in type-II structures a finite coupling between excitons of opposite spins exists already on the Hartree-Fock level and contributes to the absorption changes for the case of opposite circularly polarized pump and probe pulses.

Gain recovery dynamics in active type-II semiconductor heterostructures - Meier, Torsten; Schäfer, F.; Stein, M.; Lorenz, J.; Dobener, F.; Ngo, C.; Steiner, J. T.; Fuchs, C.; Stolz, W.; Volz, K.; Hader, J.; Moloney, J.V.; et al. (Applied Physics Letters)

Temporal sorting of optical multi-wave-mixing processes in semiconductor quantum dots - Meier, Torsten; Grisard, S.; Trifonov, A.V.; Rose, Hendrik; Reichhardt, R.; Reichelt, Matthias; Schneider, C.; Kamp, M.; Höfling, S.; Bayer, M.; Akimov, I.A (arxiv:2302.02480)

Entanglement of particles versus entanglement of fields: Independent quantum resources - Sperling, Jan; Agudelo, Elizabeth (Physical Review A)

Detector entanglement: Quasidistributions for Bell-state measurements - Sperling, Jan; Gianani, Ilaria; Barbieri, Marco; Agudelo, Elizabeth (Physical Review A)

Tracking Quantum Coherence in Polariton Condensates with Time-Resolved Tomography - Lüders, Carolin; Pukrop, Matthias; Barkhausen, Franziska; Rozas, Elena; Schneider, Christian; Höfling, Sven; Sperling, Jan; Schumacher, Stefan; Aßmann, Marc (Physical Review Letters)
Keywords: General Physics and Astronomy

Experimentelle Kompetenz Physikstudierender. Entwicklung und erste Erprobung eines performanzorientierten Kompetenzstrukturmodells unter Nutzung qualitativer Methoden - Bauer, Anna Brigitte

Selective Discrimination between CO and H2 with Copper–Ceria-Resistive Gas Sensors - Baier, Dominik; Priamushko, Tatiana; Weinberger, Christian; Kleitz, Freddy; Tiemann, Michael (ACS Sensors)
The production of hydrogen and the utilization of biomass for sustainable concepts of energy conversion and storage require gas sensors that discriminate between hydrogen (H2) and carbon monoxide (CO). Mesoporous copper–ceria (Cu–CeO2) materials with large specific surface areas and uniform porosity are prepared by nanocasting, and their textural properties are characterized by N2 physisorption, powder XRD, scanning electron microscopy, transmission electron microscopy, and energy-dispersive X-ray spectroscopy. The oxidation states of copper (Cu+, Cu2+) and cerium (Ce3+, Ce4+) are investigated by XPS. The materials are used as resistive gas sensors for H2 and CO. The sensors show a stronger response to CO than to H2 and low cross-sensitivity to humidity. Copper turns out to be a necessary component; copper-free ceria materials prepared by the same method show only poor sensing performance. By measuring both gases (CO and H2) simultaneously, it is shown that this behavior can be utilized for selective sensing of CO in the presence of H2.
Keywords: Fluid Flow and Transfer Processes; Process Chemistry and Technology; Instrumentation; Bioengineering

Understanding the Redox Mechanism of Sulfurized Poly(acrylonitrile) as Highly Rate and Cycle Stable Cathode Material for Sodium-Sulfur Batteries - Kappler, Julian; Tonbul, Güldeniz; Schoch, Roland; Murugan, Saravanakumar; Nowakowski, Michał; Lange, Pia Lena; Klostermann, Sina Vanessa; Bauer, Matthias; Schleid, Thomas; Kästner, Johannes; Buchmeiser, Michael Rudolf (Journal of The Electrochemical Society)
Room temperature sodium-sulfur (RT Na-S) batteries are considered potential candidates for stationary power storage applications due to their low cost, broad active material availability and low toxicity. Challenges, such as high volume expansion of the S-cathode upon discharge, low electronic conductivity of S as active material and herewith limited rate capability as well as the shuttling of polysulfides (PSs) as intermediates often impede the cycle stability and practical application of Na-S batteries. Sulfurized poly(acrylonitrile) (SPAN) inherently inhibits the shuttling of PSs and shows compatibility with carbonate-based electrolytes, however, its exact redox mechanism remained unclear to date. Herein, we implement a commercially available and simple electrolyte into the Na-SPAN cell chemistry and demonstrate its high rate and cycle stability. Through the application of in situ techniques utilizing electronic impedance spectroscopy (EIS) and X-ray absorption spectroscopy (XAS) at different depths of charge and discharge, an insight into SPAN’s redox chemistry is obtained.
Keywords: Materials Chemistry; Electrochemistry; Surfaces; Coatings and Films; Condensed Matter Physics; Renewable Energy; Sustainability and the Environment; Electronic; Optical and Magnetic Materials

Characterization of Na-S Battery System Using X-ray Absorption Spectroscopy - Tonbul, Güldeniz; Kappler, Julian; Murugan, Saravanakumar; Schoch, Roland; Nowakowski, Michal; Lange, Pia; Bauer, Matthias; Buchmeiser, Michael R.

Haushaltswissenschaft – Eine Diskussionsgrundlage - Küster, Christine; Klünder, Nina; Wagenknecht, Inga (Hauswirtschaft und Wissenschaft)

Large-Scale Formation of DNA Origami Lattices on Silicon - Tapio, Kosti; Kielar, Charlotte; Parikka, Johannes M.; Keller, Adrian; Järvinen, Heini; Fahmy, Karim; Toppari, J. Jussi (Chemistry of Materials)
Keywords: Materials Chemistry; General Chemical Engineering; General Chemistry

Nanoparticle‐Based Formulations of Glycopeptide Antibiotics: A Means for Overcoming Vancomycin Resistance in Bacterial Pathogens? - Pothineni, Bhanu Kiran; Keller, Adrian (Advanced NanoBiomed Research)
Keywords: General Medicine

Effect of Ionic Strength on the Thermal Stability of DNA Origami Nanostructures - Hanke, Marcel; Tomm, Emilia; Grundmeier, Guido; Keller, Adrian (ChemBioChem)
Keywords: Organic Chemistry; Molecular Biology; Molecular Medicine; Biochemistry

Stability of DNA Origami Nanostructures in Physiological Media: The Role of Molecular Interactions - Linko, Veikko; Keller, Adrian (Small)
Keywords: Biomaterials; Biotechnology; General Materials Science; General Chemistry

Structure–Reactivity Relationships in Borane-Based FLP-Catalyzed Hydrogenations, Dehydrogenations, and Cycloisomerizations - Paradies, Jan (Accounts of Chemical Research)
Keywords: General Medicine; General Chemistry

Wirtschaft neu ausrichten. Care-Initiativen in Deutschland, Österreich und der Schweiz.

Exergaming in older adults: the effects of game characteristics on brain activity and physical activity - Müller, Helen; Baumeister, Jochen; Bardal, Ellen Marie; Vereijken, Beatrix; Skjæret-Maroni, Nina (Frontiers in Aging Neuroscience)
Introduction Exergames are increasingly used in rehabilitation settings for older adults to train physical and cognitive abilities. To meet the potential that exergames hold, they need to be adapted to the individual abilities of the player and their training objectives. Therefore, it is important to know whether and how game characteristics affect their playing. The aim of this study is to investigate the effect of two different kinds of exergame (step game and balance game) played at two difficulty levels on brain activity and physical activity. Methods Twenty-eight older independently living adults played two different exergames at two difficulty levels each. In addition, the same movements as during gaming (leaning sideways with feet in place and stepping sideways) were performed as reference movements. Brain activity was recorded using a 64-channel EEG system to assess brain activity, while physical activity was recorded using an accelerometer at the lower back and a heart rate sensor. Source-space analysis was applied to analyze the power spectral density in theta (4 Hz–7 Hz) and alpha-2 (10 Hz–12 Hz) frequency bands. Vector magnitude was applied to the acceleration data. Results Friedman ANOVA revealed significantly higher theta power for the exergaming conditions compared to the reference movement for both games. Alpha-2 power showed a more diverse pattern which might be attributed to task-specific conditions. Acceleration decreased significantly from the reference movement to the easy condition to the hard condition for both games. Discussion The results indicate that exergaming increases frontal theta activity irrespective of type of game or difficulty level, while physical activity decreases with increasing difficulty level. Heart rate was found to be an inappropriate measure in this population older adults. These findings contribute to understanding of how game characteristics affect physical and cognitive activity and consequently need to be taken into account when choosing appropriate games and game settings for exergame interventions.
Keywords: Cognitive Neuroscience; Aging

Compact Metasurface-Based Optical Pulse-Shaping Device - Geromel, René; Georgi, Philip; Protte, Maximilian; Lei, Shiwei; Bartley, Tim; Huang, Lingling; Zentgraf, Thomas (Nano Letters)
Dispersion is present in every optical setup and is often an undesired effect, especially in nonlinear-optical experiments where ultrashort laser pulses are needed. Typically, bulky pulse compressors consisting of gratings or prisms are used to address this issue by precompensating the dispersion of the optical components. However, these devices are only able to compensate for a part of the dispersion (second-order dispersion). Here, we present a compact pulse-shaping device that uses plasmonic metasurfaces to apply an arbitrarily designed spectral phase delay allowing for a full dispersion control. Furthermore, with specific phase encodings, this device can be used to temporally reshape the incident laser pulses into more complex pulse forms such as a double pulse. We verify the performance of our device by using an SHG-FROG measurement setup together with a retrieval algorithm to extract the dispersion that our device applies to an incident laser pulse.
Keywords: Mechanical Engineering; Condensed Matter Physics; General Materials Science; General Chemistry; Bioengineering

Hard carbon microspheres with bimodal size distribution and hierarchical porosity via hydrothermal carbonization of trehalose - Wortmann, Martin; Keil, Waldemar; Diestelhorst, Elise; Westphal, Michael; Haverkamp, René; Brockhagen, Bennet; Biedinger, Jan; Bondzio, Laila; Weinberger, Christian; Baier, Dominik; Tiemann, Michael; Hütten, Andreas; et al. (RSC Advances)
Hydrothermal carbonization (HTC) is an efficient thermochemical method for the conversion of organic feedstock to carbonaceous solids. HTC of different saccharides is known to produce microspheres (MS) with mostly Gaussian size distribution, which are utilized as functional materials in various applications, both as pristine MS and as a precursor for hard carbon MS. Although the average size of the MS can be influenced by adjusting the process parameters, there is no reliable mechanism to affect their size distribution. Our results demonstrate that HTC of trehalose, in contrast to other saccharides, results in a distinctly bimodal sphere diameter distribution consisting of small spheres with diameters of (2.1 ± 0.2) μm and of large spheres with diameters of (10.4 ± 2.6) μm. Remarkably, after pyrolytic post-carbonization at 1000 °C the MS develop a multimodal pore size distribution with abundant macropores > 100 nm, mesopores > 10 nm and micropores < 2 nm, which were examined by small-angle X-ray scattering and visualized by charge-compensated helium ion microscopy. The bimodal size distribution and hierarchical porosity provide an extraordinary set of properties and potential variables for the tailored synthesis of hierarchical porous carbons, making trehalose-derived hard carbon MS a highly promising material for applications in catalysis, filtration, and energy storage devices.
Keywords: General Chemical Engineering; General Chemistry

Ultrafast Proton Transfer Pathways Mediated by Amphoteric Imidazole - Codescu, M.-A.; Kunze, T.; Weiß, M.; Brehm, Martin; Kornilov, O.; Sebastiani, D.; Nibbering, E. T. J. (J. Phys. Chem. Lett.)